2008
DOI: 10.1111/j.1472-765x.2008.02467.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TEMPO®EC and TBX medium for the enumeration ofEscherichia coliin cheese

Abstract: Aims:  TEMPO® EC (Escherichia coli) is based on glucuronidase activity and is a test for use with the TEMPO system for the automated 24 h enumeration of E. coli in food products. In this study, TEMPO EC was compared with TBX medium, the current standard plate method for the enumeration of E. coli in cheese. Methods and Results:  For comparative purposes, both naturally (92) and artificially contaminated (31) cheese samples were studied. Pearson correlation coefficients were determined as 0.954 and 0.978 betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…The automated TEMPO system has been developed to replace the disadvantages of the traditional MPN method. Previous studies have shown that there is a remarkable correlation between the TEMPO and standard methods in various naturally contaminated samples at the same culture conditions (Paulsen et al 2006(Paulsen et al , 2008Kunicka 2007;Kobayashi et al 2008;Torlak et al 2008;Crowley et al 2009Crowley et al , 2010Owen et al 2010). Therefore, the culture condition on the detection might not influence the experimental data even if there might be some difference in growth rate and the injury of bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The automated TEMPO system has been developed to replace the disadvantages of the traditional MPN method. Previous studies have shown that there is a remarkable correlation between the TEMPO and standard methods in various naturally contaminated samples at the same culture conditions (Paulsen et al 2006(Paulsen et al , 2008Kunicka 2007;Kobayashi et al 2008;Torlak et al 2008;Crowley et al 2009Crowley et al , 2010Owen et al 2010). Therefore, the culture condition on the detection might not influence the experimental data even if there might be some difference in growth rate and the injury of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…TEMPO is an automated system based on the most probable number (MPN) method for enumeration of aerobic bacteria and specific pathogens in foods (Paulsen et al 2006(Paulsen et al , 2008Kunicka 2007;Kobayashi et al 2008;Torlak et al 2008;Crowley et al 2009Crowley et al , 2010Owen et al 2010). It is seen as an internationally recognized method validated by EN ISO 16140 and the AOAC Research Institute and has been evaluated in various kinds of food matrices (Crowley et al 2009(Crowley et al , 2010Jasson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have compared the TEMPO automated MPN procedure with traditional methods for enumeration of aerobic mesophiles or Enterobacteriaceae from various foods (2,8,9,13) and enumeration of E. coli from cheese or other foods (1,15). Generally, the agreement between the enumeration methods has been close.…”
Section: Resultsmentioning
confidence: 99%
“…The ready-to-use TEMPO system (bioMérieux, Marcy l'Etoile, France) is a modified culture method that makes use of vials with culture medium specific to the test and cards simulating the most-probablenumber method. It is based on an automated system that reduces workload and number of manipulations without the necessity of a full laboratory infrastructure (Torlak et al, 2008;Jasson et al, 2010). The aim of this communication is to compare the flow cytometry and the automated most-probable-number method to standard plate count measurements and to each other, and to suggest the most appropriate rapid method to measure the TVC in this epidemiological setting.…”
Section: Short Communicationmentioning
confidence: 99%